The Differences in The Consumption of Soy Milk and Green Bean Juice on Breast Milk Production Among Postpartum Women at The Health Center of Tangerang Regency - Bunga Tiara Carolin; Retno Widowati; Dewi Rahmawati (Healthy-Mu Journal, 2022)
Based on data from a preliminary study conducted at the Sukadiri health centre, from 10 postpartum women for 4-7 days who were interviewed, it was found that 7 postpartum women experienced non-smooth production of breast milk caused by nutritional factors where the mother did not know what foods could facilitate breastfeeding. Meanwhile, 3 postpartum women produced breast milk smoothly. This tudy to determine the differences in the consumption of soy milk and green bean juice on breast milk production among postpartum women at the Sukadiri Health Center, Tangerang Regency. This study was a Quasi Experiment study with a pretest-post test control group design. The research sample was 30 people, with a purposive sampling technique. The research instrument used a questionnaire. Data analysis used univariate and bivariate analysis, with dependent t test and independent t test. The results of the dependent t test on postpartum women who consumed soy milk with a p value of 0.000 and postpartum women who consumed green bean juice p value was 0.000. Meanwhile, the results of the independent t test between groups found that there was no difference between the consumption of soy milk and green bean juice on breast milk production in postpartum women with a p value of 0.162. There is an increase in milk production in women who consume soy milk and consume who consume green bean juice. Whereas in the two intervention groups there was no difference, which means that if the women is bored with soy milk, she can consume green bean juice, because both soy milk and green bean juice can increase the milk production of postpartum women. Therefore, it is hoped that the Health Centre will be able to provide non-pharmacological therapies that are useful in increasing breast milk production in post-partum women who are breastfeeding with soy milk or green bean juice programs.